Assessing the Impact of the First Feeding Practice on Wasting Risk Among Indonesian Children Under the Age of Five - Azrimaidaliza, Azrimaidaliza; Apriliani, Annisa Dwi; Kusuma, Mutiara Tirta Prabandari Lintang (UI Scholars Hub, 2025)
The problem of undernutrition among children under the age of five (the under-five) continues to be alarmingly high in Indonesia, including in West Sumatra Province. Various factors contribute to this issue, with studies suggesting a relationship between intergenerational causes and undernutrition. This study analyzed the main risk factors of wasting among children in Padang City. Data were collected from 174 under-five and divided into unmatched cases that were selected randomly and control groups. The mothers were interviewed using a questionnaire regarding their children’s feeding habits, and weight and height data were collected from primary health care. Multiple logistic regression analysis was used to calculate the odds ratio for undernutrition. The findings revealed that 37.6% of the under-five were breastfed, whereas over half received inadequate complementary feeding. Poor breastfeeding practices (p-value = <0.001; OR = 8.389; 95% CI 2.611–14.432) and inadequate complementary feeding (p-value = <0.001; OR = 13.534; 95% CI 6.025–30.400) were identified as major contributors to the increased risk of undernutrition in the under-five. The high prevalence of suboptimal under-five feeding practices in the study area highlights the necessity of enhancing maternal nutrition education to ensure optimal growth and nutrition.